Pengembangan dan Validitas Instrumen Perilaku Asertif Pada Siswa SMP - Fauziah, Mufied; Siswantari, Heni; Nabila, Hurin; Setyowati, Aprilia; Rifqoh, Fany (Universitas Mathla'ul Anwar Banten, 2024)
Teenagers have a strong interest in being accepted by their peers, so some teenagers have difficulty behaving assertively. The aim of this research is to obtain an inventory that can be used to determine the level of assertive behavior in junior high school students. This research adapts the Gregory model instrument development steps which consist of defining tests, selecting scales, constructing items, testing items, revising, and developing norms. The instrument was developed from Alberti and Emmons' theory which reveals that aspects of assertive behavior are the ability to do something according to one's abilities, express oneself, defend oneself, express opinions and respect the rights of others. The assessment of the instrument developed was carried out based on input from two experts and trials carried out on 137 students in the city of Yogyakarta. Data analysis was carried out qualitatively based on expert input and quantitatively to test the validity and reliability of the instrument using the RASCH model. This research produces an inventory of assertive behavior that has been declared appropriate by experts, with reliability in the sufficient category, the quality of statement items in the special category and statement items declared to have model fit. It is hoped that the inventory developed can be used by guidance and counseling teachers in identifying students' assertive behavior so that it can be used as consideration in preparing service programs.